2011
DOI: 10.1126/science.1199484
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis Identifies Grb10 as an mTORC1 Substrate That Negatively Regulates Insulin Signaling

Abstract: The evolutionarily conserved Ser-Thr kinase mTOR plays a critical role in regulating many pathophysiological processes. Functional characterization of the mTOR signaling pathways, however, has been hampered by the paucity of known substrates. We used large-scale quantitative phospho-proteomics experiments to define the signaling networks downstream of mTORC1 and mTORC2. Characterization of one mTORC1 substrate, the growth factor receptor-bound protein 10 (Grb10), showed that mTORC1-mediated phosphorylation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
801
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 780 publications
(846 citation statements)
references
References 16 publications
27
801
2
6
Order By: Relevance
“…The small response at the phosphoproteome level detected here is quite different from global quantitative phosphoproteomics studies that use cellular stimuli to directly regulate a particular kinase [72][73][74][75] or those studying cellular processes known to be greatly dependent on phosphorylation. 18,76 Much greater effects on phosphorylation throughout the entire signaling cascade are also observed, as expected.…”
Section: View Article Onlinementioning
confidence: 66%
“…The small response at the phosphoproteome level detected here is quite different from global quantitative phosphoproteomics studies that use cellular stimuli to directly regulate a particular kinase [72][73][74][75] or those studying cellular processes known to be greatly dependent on phosphorylation. 18,76 Much greater effects on phosphorylation throughout the entire signaling cascade are also observed, as expected.…”
Section: View Article Onlinementioning
confidence: 66%
“…In contrast, we observe that both pharmacological and genetic inhibition of mTORC1 evokes spontaneous pain, mechanical hypersensitivity, and increased sensory neuron excitability (Melemedjian et al 2013). Rapamycin releases the feedback inhibition of Grb10, which is an upstream regulator of MAPK pathway (Kebache et al 2007;Hsu et al 2011;Yu et al 2011) and has previously been shown to increase ERK activation in TSC2 −/− murine embryonic fibroblasts (Ghosh et al 2006).…”
Section: Discussionmentioning
confidence: 81%
“…However, the molecular mechanism underlying the integration of multiple signaling elements to produce a concerted response to insulin and IGF is largely unknown. Previous studies have demonstrated that mTOR is tightly involved in IGF-IR and InsR signaling, either as an effector or regulator of several key elements in signaling pathway [6,14,18,19]. mTORC1 and its substrate S6K1 promote IRS1 degradation, thereby negatively regulate IGF-IR and InsR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 and its substrate S6K1 promote IRS1 degradation, thereby negatively regulate IGF-IR and InsR signaling. Recently, Grb10, an adaptor protein that negatively regulates InsR and IGF-IR, has been identified as an mTORC1 substrate that is stabilized by mTORC1 [18,19]. mTORC2 positively regulates Akt and ERK, two key elements in IGF-IR/InsR signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation